CYTOLOGICAL AND GENETIC CHARACTERIZATION OF A NEW MUTANT OF VEGETABLE PEPPER CAPSICUM ANNUUM VAR. ANNUUM L. - O. Yu. Timin; O. O. Timina; P. Yu. Montvid; A. P. Samovol (Вавиловский журнал генетики и селекции, 2015)
Two new spontaneous mutations of the vegetable pepper C. annuum var. annuum have been identified in the 5-th insolation zone in a greenhouse. Tentative cytologic and genetic characterization shows that both were dominant and were controlled by two separately inherited single factors. The mutation manifested at the cotyledon stage is lethal, and the other belongs to basic chromosome mutations, causing a reduced viability of the homozygote. It is characterized by a specific spectrum and frequency of chiasmata and chromosomal aberrations. It depends on the gene dose. Application of the new mutation in pure breeding and genetic research of vegetable pepper is discussed.